Gallic acid enhances reproductive function by modulating oxidoinflammatory and apoptosis mediators in rats exposed to aflatoxin-B1 (2020)
Aflatoxin B1 (AFB1) is reported to elicit adverse reproductive outcomes in animals. Gallic acid (GA) is known to exhibit antioxidant and inflammatory bioactivities. The impact of GA on AFB1-facilitated reproductive dysfunction is nonexistent in literature. This investigation elucidated GA protective effect on AFB1-induced reproductive toxicities in rats, exposed for 28 consecutive days to AFB1 (75 mg/kg), or co-treated with GA (20 or 40 mg/kg) body weight. AFB1 significantly (p<0.05) reduced testicular function biomarkers, serum hormonal levels, and functional sperm characteristics in experimental animals. GA abated AFB1-induced increases (p<0.05) in lipid peroxidation and reactive oxygen and nitrogen species, suppressed myeloperoxidase, interleukin-1b, nitric oxide, and tumor necrosis factor-a levels—inflammatory biomarkers—in testes, epididymis, and hypothalamus. Furthermore, GA improved antioxidant defenses and alleviated reduction in interleukin-10, caspase-3 activation, and histological variations in epididymis, testes, and hypothalamus of rats dosed with AFB1. Conclusively, GA enhanced reproductive function in AFB1-exposed rats by modulating inflammatory, oxidative stress, and apoptosis mediators.